Estimating the number of people who inject drugs in Australia - Sarah Larney; Matthew Hickman; Rebecca Guy; Jason Grebely; Gregory J. Dore; Richard T. Gray; Carolyn A. Day; Jo Kimber; Louisa Degenhardt (BMC, 2017)
Abstract Background Injecting drug use is associated with considerable morbidity and mortality. Estimates of the size of the population of people who inject drugs are critical to inform service planning and estimate disease burden due to injecting drug use. We aimed to estimate the size of the population of people who inject drugs in Australia. Methods We applied a multiplier method which used benchmark data (number of people in opioid substitution therapy (OST) on a snapshot day in 2014) and multiplied it by a factor derived from the prevalence of current OST among people who inject drugs participating in the Australian Needle and Syringe Program Survey in 2014. Estimates of the total population of people who inject drugs were calculated in each state and territory and summed to produce a national estimate. We used the sex and age group distribution seen in datasets relating to people who inject drugs to derive sex- and age-stratified estimates, and calculated prevalence per 1000 population. Results Between 68,000 and 118,000 people aged 15-64 years inject drugs in Australia. The population prevalence of injecting drug use was 6.0 (lower and upper uncertainty intervals of 4.3 and 7.6) per 1000 people aged 15-64 years. Injecting drug use was more common among men than women, and most common among those aged 35-44 years. Comparison of expected drug-related deaths based on these estimates to actual deaths suggest that these figures may be underestimates. Conclusions These are the first indirect prevalence estimates of injecting drug use in Australia in over a decade. This work has identified that there are limited data available to inform estimates of this population. These estimates can be used as a basis for further work estimating injecting drug use in Australia.